Corporation tax statistics from the records of the revenue commissioners - Gillanders, Norman (Statistical and Social Inquiry Society of Ireland, 1993)
The Revenue Commissioners' head office is in Dublin Castle. Some of the staff there are engaged in typical head office functions such as personnel, accounting and computer systems. Others have overall responsibility for administration of the various taxes and duties. Finally, there is a small group of civil servants in a number of sections who have responsibility for advising Revenue's top management on all aspects of taxation policy. These budget and planning sections monitor the operation of existing tax law and suggest improvements where necessary. Part of this job involves making quite detailed estimates of the budgetary cost of, or yield from, changes in taxation policy. These sections obviously have close working links with the Department of Finance which has the primary policy-making role in the fiscal area. The corporation tax statistics which are the subject of this paper are produced in the Legislation and Statistics section of the Revenue Commissioners' head office. The section has responsibility for planning and policy for income tax, corporation tax and capital gains tax. The statistics unit of Legislation and Statistics has a staff of 10.
Read before the Society, 11 February 1993
Keywords: Corporation tax; Taxation rates; Revenue Commissioners; 314.15